KESADARAN WAJIB PAJAK, PENGETAHUAN PAJAK, SANKSI PERPAJAKAN PENGARUHNYA TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR - Lidia Andiani; Mirfad Abdat; Muniroh Muniroh (Universitas Riau Kepulauan, 2023)
This research aims to examine taxpayer awareness, tax knowledge, tax sanctions and their influence on motor vehicle taxpayer compliance through public service accountability. This research was conducted in Blimbing District, Malang City. The sampling method in this research uses the Nonprobability sampling method using the Proportional sampling technique. Determination of the sample size was calculated using the Slovin formula using 100 samples. The analysis method uses descriptive statistical analysis and linear regression. This type of research is quantitative causality research and data analysis using SPSS. In testing the hypothesis model, we use a multiple linear regression test. The research results show that taxpayer awareness, tax knowledge, tax sanctions have no effect on motor vehicle taxpayer compliance.